IMPACT OF SELF-SUFFICIENCY FISH FEED PROGRAM ON THE FISH FARMING BUSINESS PERFORMANCE - Sari Rachmawati; Nunung Kusnadi; Netti Tinaprilla (Agrisocionomics: Jurnal Sosial Ekonomi Pertanian, 2023)
High feed prices and a high proportion of feed costs cause the profitability of fish farming businesses to decline. One of the government's efforts to reduce feed costs is encouraging fish farmers to produce their feed using local raw materials through Self-Sufficiency Fish Feed Program. This study aims to analyze program’s impact on the fish farming performance using the Propensity Score Matching (PSM) method. Performance is measured by cost, revenue, profit, R/C ratio, Feed Conversion Ratio (FCR), and technical efficiency which estimated using Data Envelopment Analysis (DEA). The results show that program implementation at the fish farmer's level has not positively impacted the fish farming business's performance. The results of the PSM analysis show that the program significantly impacts on costs, revenue, profit, R/C ratio, FCR, and technical efficiency. Farmers with programs have a higher average cost and FCR than farmers without programs. The fish farmers with program have a lower revenue, profit, R/C ratio and technical efficiency than fish farmers without program. From the results of this study, it can be concluded that the main cause the program has not had a positive impact on the fish farming businesses performance is the quality of self-sufficiency fish feed. Therefore, the recommended policy is to create a system for supplying local raw materials with good quality, increasing feed formulation training and need specialize by forming group of self-sufficiency fish feed producers separated from the fish farming group.